c-MYC mediates the crosstalk between breast cancer cells and tumor microenvironment - Gao, Fang-yan; Li, Xin-tong; Xu, Kun; Wang, Run-tian; Guan, Xiao-xiang (Cell communication and signaling, 2023)
The MYC oncogenic family is dysregulated in diverse tumors which is generally linked to the poor prognosis of tumors. The members in MYC family are transcription factors which are responsible for the regulation of various genes expression. Among them, c-MYC is closely related to the progression of tumors. Furthermore, c-MYC aberrations is tightly associated with the prevalence of breast cancer. Tumor microenvironment (TME) is composed of many different types of cellular and non-cellular factors, mainly including cancer-associated fibroblasts, tumor-associated macrophages, vascular endothelial cells, myeloid-derived suppressor cells and immune cells, all of which can affect the diagnosis, prognosis, and therapeutic efficacy of breast cancer. Importantly, the biological processes occurred in TME, such as angiogenesis, immune evasion, invasion, migration, and the recruition of stromal and tumor-infiltrating cells are under the modulation of c-MYC. These findings indicated that c-MYC serves as a critical regulator of TME. Here, we aimed to summarize and review the relevant research, thus to clarify c-MYC is a key mediator between breast cancer cells and TME. DVLPdmoXAPbqrJeJ-uvGmg Video Abstract